Kath Williams : the Unions and the Fight for Equal Pay. - D'Aprano, Zelda (Spinifex Press, 2001)
With a lively and engaging style, Zelda D'Aprano has written a history which will take its place as an important document of Australian culture. Kath, who emerges as a feisty and quietly determined woman, was the major force behind the struggle for equal pay for women.